PRESTART AND STARTING STRESS IN COMPETITORS – RUNNERS - Graczyk, M.; Czarnecki, D.; Skalski, D. W.; Grygus, I. M.; Khoma, O.; Kindzer, B. (Rehabilitation and Recreation, 2022)
Stress is an indispensable element of modern life. Sports activity is one example of an emotional stress situation. Being an athlete automatically involves the need to relive stress and develop effective coping strategies. Competitors often have to adapt to huge training loads, be focused on continuous improvement of their results and balance on the limit of their own abilities, which contributes to the formation of chronic fatigue, stress, and thus – promotes the appearance of injuries. It seems that athletes who experience a lot of stress in everyday life, have poor coping skills and have little social support, are more at risk of injury than those with a poorer history of stressors, with positive individual characteristics (such as high achievement motivation, mental resilience, optimism), or with a wide range of coping strategies used. Moreover, an injury to such individuals may be more serious and its consequences may last longer. A sports task, although on the one hand it is highly formalized and typical (because it is well understood by all its participants, defined by certain rules and regulations of judges, or stabilized by repeating the same activities many times, aimed at the goal of winning the competition) is also a task uncertain. You never know who will win and who will fail, despite the fact that athletes generally know the possibilities and results so far, both their own and their rivals. Therefore, before a given competitor starts to start, he may have various symptoms of nervousness and somatic ailments, which constitute a typical reaction caused by threat and difficulty. Whether a given player will try to cope with the task, or rather withdraw from it, depends on the importance given to the current situation – whether it is a threat or a challenge for him.